La rebelión y el movimiento indígena en el Ecuador durante el año 2019 - Rojas-Cárdenas, Juan Alberto; Díaz-Ayavaca, Carla Yamilex; Sánchez-Parreño, Josué Alfredo (IUSTITIA SOCIALIS, 2021)
La rebelión y el movimiento indígena en el Ecuador durante el año 2019